2021
DOI: 10.52711/0974-360x.2021.00646
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical, Phytochemical and Fluorescence analysis of the plant Bougainvillea spectabilis (Willd.)

Abstract: Objective: The aim of the study is to investigate the Phytochemical, Pharmacognostical, Fluorescence analysis and heavy metal testing of the plant Bougainvillea spectabilis (WILLD.). Methods: The plant powder was extracted with different solvents such as petroleum ether, chloroform, ethyl acetate, ethanol, and water. The different extracts were tested qualitatively for the identification of various phytochemical constituents. The plant powder was subjected to fluorescence analysis in daylight and in ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This may be because, in comparison to the aqueous extract, the ethanolic B. spectabilis extract contains more flavonoids and saponins, giving it a distinct advantage. [25] The existing research, however, fails to elucidate the specific constituents or mechanisms by which the B. spectabilis plant reduces the progression of duodenal ulcers. Research on gross anatomy and histology has demonstrated, to a certain degree, the efficacy of both the standard and ethanolic extracts in restoring the structure of the stomach and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because, in comparison to the aqueous extract, the ethanolic B. spectabilis extract contains more flavonoids and saponins, giving it a distinct advantage. [25] The existing research, however, fails to elucidate the specific constituents or mechanisms by which the B. spectabilis plant reduces the progression of duodenal ulcers. Research on gross anatomy and histology has demonstrated, to a certain degree, the efficacy of both the standard and ethanolic extracts in restoring the structure of the stomach and duodenum.…”
Section: Discussionmentioning
confidence: 99%
“…The ash value, extractive value, and loss on drying (LOD) of the drug were assessed using the method provided in the British Pharmacopoeia [15] for physicochemical investigations. The method developed by Kokoshi et al and Das et al [16,17] was used to analyze the fluorescence of powdered drugs. A 1mg powder drug was placed on a microslide and subjected to UV and daylight to study the drug's luminous properties.…”
Section: Physico-chemical Analysismentioning
confidence: 99%